Young Astronaut (India Pegasus, 2020)
Give flight to children's imagination and aspirations with this wonderful series. The colourful, cutely illustrated book in this series cover all kinds of jobs people do. The series uses simple, everyday words to familiarise children with various professions and encourages them to develop a healthy respect for each of the jobs and the hard work required to do them
The World Around Us
Keywords: General Knowledge